In-Situ Condition Monitoring of Components in Small Modular Reactors Using Process and Electrical Signature Analysis - Victor Lollar (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2013)
Components in small modular reactors (SMRs) are located in a hazardous environment and must be monitored remotely. Electrical signature analysis (ESA) is a viable option for component monitoring as it can be implemented on-line away from the actual equipment. This research attempts to use both electrical signatures from a pump motor and process variables such as flow and pressure to effectively monitor reactor components. An experimental flow loop with pump health monitoring equipment and a data acquisition system was used for experiments. Process variables analyzed include pressure, flow rate, water level, and motor vibrations. The electrical signatures monitored were the motor current and voltage drawn. It was observed that the pressure in the loop, vibration, flow and motor current signals show similar behavior in the transient region (start-up and shut-down) as well as during steady-state operation. It was demonstrated that a strong relationship exists between motor current and process variables such as flow, pressure, and motor vibrations. These relationships will be used to prove that the pump’s electrical signatures can be used to monitor the pump, flow, and pressure without direct measurement of the process variables.
Keywords: Small Modular Reactors; Nuclear Power